Expanding phenotype of mitochondrial depletion syndrome in association with TWNK mutations. (May 2019) - Sukhudyan, Biayna; Gevorgyan, Ani; Sarkissian, Ashot; Boltshauser, Eugen
Abstract: Mitochondrial DNA depletion syndromes (MDS) are a group of clinically and genetically heterogeneous autosomal recessive disorders characterized by a reduction of mtDNA. We report two siblings of Armenian origin with early onset neurodegenerative disease characterized by encephalopathy, severe hypotonia, facial dyskinetic movements, abnormal eye movements, severe failure to thrive, and abnormal renal and hepatic function. Sanger sequencing confirmed two variants in the C10orf2 gene (TWNK) and indicated a diagnosis of MDS. Our recent observation confirms that nephrocalcinosis and proximal tubulopathy can be a part of a clinical picture of MDS associated with TWNK mutations and document peculiar ocular and orobuccolingual dyskinesias. Wrist myoclonia and tongue tremor were new clinical features in our patients. We suggest that the above-mentioned clinical constellation could potentially provide the basis for the diagnosis of MDS. Highlights: Wrist myoclonia and tongue tremor are new clinical features of mitochondrial depletion syndromes. Proximal tubulopathy and nephrocalcinosis can be observed in TWNK mutations. Peculiar constellation of clinical symptoms can provide targeted genetic testing for mitochondrial depletion sydromes.